METODE SAVI MENGGUNAKAN MEDIA ANIMASI UNTUK PEMBELAJARAN POLA KALIMAT BAHASA JEPANG LEVEL DASAR PADA SISWA SMA - LESTARI, DINA (HIKARI, 2020)
?? ????????????SAVI??????????????????????????????????????????????????????????????????????????????????? ???????? (1) ???????????????????????????????????????SAVI???????????????(2) SAVI???????????????????????????????? ???????????????????????????? ??????????????????1?????SAVI????????????????????????SAVI?????????????????????????????????????(2) SAVI????????????????????????????????????????????????????????????????????????????SAVI?????????????????????????????????????????????????????SAVI????????????????????????????? ???????????????SAVI??? ABSTRACT Learning to sentence patterns of the Japanese language using the method of learning SAVI with media animation is based on theory of accelerated learning. Theories about learning involving active learning activities to produce a change.The purpose of this article are: (1) describe the importance of learning methods SAVI using media animation in learning to sentence patterns of Japanese language at high school students, and (2) describe the animation medium in accordance with the methods of learning SAVI. The research method used in this research is a research literature review. The results of the analysis in this study, namely (1) the method of learning SAVI is learning that maximize the use of the five senses, in addition, the element in the cognitive, affective, and psychomotor incorporated into one in the process of learning with the use of the SAVI method; (2) the animation medium in accordance with the methods of learning SAVI namely in the form of audio visual media. The audio-visual media function as a mediator of learning, and has to include elements of SAVI in the form of auditory and visual. It can then be combined in the learning process, by developing the bodys movements and understanding, so that all elements of SAVI are fulfilled. Keywords: learning method, learning method SAVI, sentence patterns